Continuous Complete Remission in Two Patients with Acute Lymphoblastic Leukemia and Severe Fungal Infection Following Short-Term, Dose-Reduced Chemotherapy - Lüke, Florian; Harrer, Dennis C.; Hahn, Joachim; Grube, Matthias; Pukrop, Tobias; Herr, Wolfgang; Reichle, Albrecht; Heudobler, Daniel (Frontiers in Pharmacology, 2021)
Spontaneous remission in acute lymphoblastic leukemia (ALL) is a rare phenomenon. This typically involves a pattern of feverish or septic disease, followed by quick but mostly transient remission. We report on two male patients, 46-year-old (pt. 1) and 19-year-old (pt. 2), both with CD20 positive, BCR-ABL negative common B-ALL. Patient 1 had received dexamethasone and cyclophosphamide (1.2 g) as a prephase therapy, followed by rituximab and cumulative 200 mg daunorubicin combined with 2 mg vincristine as an induction therapy. Patient 2 was treated with a reduced therapy regimen (Vincristine 1 mg, dexamethasone and 80mg daunorubicin, 12-month mercaptopurine maintenance) due to (alcohol-related) toxic liver failure and pontine myelinolysis. Both patients developed severe septic disease just a few days into induction treatment. Patient 1 suffered from pulmonary mycosis, which in the end had to be resected. Histological work-up revealed invasive mucor mycosis. Patient 2 presented with elevated serum aspergillus antigen and radiographic pulmonary lesions, strongly hinting at pulmonary mycosis. In both patients, chemotherapy had to be interrupted and could not be resumed. Both patients recovered under broad antimicrobial, antifungal and prophylactic antiviral therapy and achieved molecular complete remission, which has been on-going for 34 months (patient 1) and eight years (patient 2), respectively. Short-term, reduced intensity induction chemotherapy accompanied by severe fungal infections was followed by long-lasting continuous complete remissions in ALL. The course of the presented cases shows that infection-associated immunogenic responses may not only limit apoptosis induced-regrowth of leukemia i.e. via the ‘phoenix rising pathway’ but could also eradicate minimal residual disease. This clinical observation is in line with experimental data showing that durable toll-like receptor-induced protection against B-ALL outgrowth is possible via activation of innate immune response in the bone marrow. The effects of combined cytotoxic therapy and severe infection may also be mimicked by biomodulatory treatment strategies aiming at reorganizing pathologically altered cellular signaling networks. Correcting dysregulated homeostatic pathways with biomodulatory acting drugs could reduce toxicity and comorbidity in adult patients. Therefore, the two cases should encourage systematic studies on how leukemia stroma interaction can be harnessed for achieving long lasting ALL control.